Vyacheslav Alexeevich Zemsky (21.08.1919 – 17.11.2012) (Вестник зоологии, 2013)
Vyacheslav Alexeevich Zemsky, world-renowned marine mammal scientist and expert died peacefully at his home in Moscow, with his son Andrey by his side, on Saturday, November 17. He was 93.